Analysis of genomic copy number variations through whole-genome scan in Chinese Qaidam cattle - Liu, Yangkai; Mu, Yanan; Wang, Wenxiang; Ahmed, Zulfiqar; Wei, Xudong; Lei, Chuzhao; Ma, Zhijie (Frontiers in Veterinary Science, 2023)
Qaidam cattle (CDM) is an indigenous breed inhabiting northwest of China. Here, we newly sequenced 20 Qaidam samples to investigate the copy number variants (CNVs) based on the ARS-UMD1.2 reference genome. We generated CNV region (CNVR) datasets to explore the genomic CNV diversity and population stratification. Four other northern Chinese cattle breeds (Xizang cattle, XZ; Kazakh cattle, HSK; Mongolian cattle, MG; and Yanbian cattle, YB) embracing 43 genomic sequences were collected, and are distinguished from each divers population by deletions and duplications. We also observed that duplications are significantly more than deletions in the genome, which may be less harmful to gene formation and function. At the same time, only 1.15% of CNVRs overlapped with the exon region. Population differential CNVRs and functional annotations between Qaidam poplation and others uncovered functional genes related to immunity (MUC6), growth (ADAMTSL3) and adaptability (EBF2). Our analysis has provided numerous genomic characteristics of Chinese cattle, which are valuable to customized biological molecular markers in cattle breeding and production.